Notes on Early Land Plants Today. 32. New synonyms in Andrewsianthus and a transfer to Tritomaria (Lophoziaceae, Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Konrat, Matt Von (Phytotaxa, 2013)
Andrewsianthus Schuster (1961: 66) is a heterogeneous complex. Most taxa have bilobed leaves, but there are also taxa with trilobed leaves [Andrewsianthus ferrugineus Grolle (1966: 275) and sometimes also Andrewsianthus sundaicus (Schiffner 1898: 202) Schuster 1969: 710)] and unlobed leaves [Andrewsianthus cavifolius Váňa (1974: 640), Andrewsianthus mizutanii Kitagawa (1969: 307) and Andrewsianthus zantenii Váňa (1974: 645)].